Laparoscopic intragastric resection of gastric synovial sarcoma: report of the first ever case with video demonstration - Matteo Rivelli; Eduardo Fernandes; Cristian Conti; Laura Bernardoni; Sara Pecori; Sara Cingarlini; Corrado Pedrazzani (World Journal of Surgical Oncology, 2021)
Abstract Background Synovial sarcoma (SS) is a rare soft tissue tumor. Among different anatomical locations where it can be found, gastric localization is a very uncommon one. Based on soft tissue sarcoma guidelines, complete tumor excision is considered the main treatment approach. Depending on size and localization of the tumor, both wedge and major gastric resections have been performed in the past for the treatment of this condition. Case presentation We present the case of a 43-year-old woman who underwent a laparoscopic intragastric excision of a gastric 10-mm SS located nearby the esophagogastric junction. Pathology examination confirmed the presence of a SS. The resected specimen confirmed margin-free excision of a monophasic spindle cell neoplasm invading the submucosa and presenting the rearrangement of SS18 gene at fluorescence in situ hybridization (FISH). No adjuvant treatment was offered, and 18 months after surgery, the patient was alive and disease free. Conclusions This represents the first case reported in literature of a laparoscopic intragastric resection for a gastric SS. This approach allowed to obtain a full thickness radical tumor resection with the advantages of minimally invasive and organ preserving surgery.